Analysis of Ruling T-025/2004 by the Constitutional Court of Colombia Declaring the Unconstitutional Status Quo Regarding the Protection of Rights of Armed Displacement Victims in the Framework of the Colombian Internal Conflict: por parte de la Corte Constitucional de Colombia frente a la protección tutelar de los derechos de las víctimas de desplazamiento armado en el marco del conflicto interno colombiano - Palacios- Salcedo, Cleider Andrés (DIXI, 2018)
Aim: To carry out an exhaustive analysis of Ruling T-025/2004 and the respective monitoring orders issued by the Constitutional Court of Colombia, aimed at establishing whether to date the Court’s declaration of unconstitutional status quo has helped the executive implement serious policies to improve the quality of life of forced displacement victims. Methods: Information from formal sources and internationally recognized documents was compiled as reference literature and the data collected were analyzed. In group discussions, the deepest issues related to the topic were resolved, unifying interpretative criteria that led to group conclusions and recommendations to finally complete the writing of this article. Results: It is noted that, after Ruling T-025/04, the Government has been obliged to promote policies aimed at assisting the victims; the Court’s monitoring has been vital to materialize everything provided in the ruling. Conclusions: The declaration of unconstitutional status quo has been an important breakthrough in the recognition of victims as subjects of rights and duties and of special protection; today important progress has been made in the matter.